Safety professional's reference and study guide - Yates, W. David (CRC Press : Taylor & Francis Group, 2025)
For safety professionals navigating the complexities of safety practices daily, the search for a single-source guide covering diverse topics has been an ongoing quest. Now, in its fourth edition, Safety Professional’s Reference and Study Guide has expanded its scope, incorporating crucial new chapters on legal aspects of the safety profession, recordkeeping, sustainability principles, and more, catering to the evolving needs of the Environmental Health and Safety (EHS) community.This title is every safety professional’s indispensable, market-leading resource, empowering the reader to tackle challenges with confidence and expertise. Exploring core aspects of occupational safety, this book offers a wealth of knowledge, each chapter offering practical insights and actionable advice. The title goes beyond conventional boundaries, addressing emerging topics such as electrical safety, risk assessment, and sustainability principles in brand-new chapters.A go-to guide for any practicing safety professional seeking a quick desk reference, a student supplementing their textbooks, or a candidate preparing for certification exams including ASP, CSP, OHST or CHST, it equips readers with the knowledge and skills needed to navigate the evolving landscape of occupational safety focusing on real-world applications and exam readiness